2015
DOI: 10.15356/2076-6734-2015-2-69-80
|View full text |Cite
|
Sign up to set email alerts
|

GIS- and field data based modeling of snow water equivalent in shrub tundra

Abstract: Рассматривается методика моделирования водного эквивалента снежного покрова, основанная на статистической обработке данных полевой снегомерной съёмки и геоинформационном анализе различных параметров: рельефа, направления ветра, кустарниковой растительности. Установлено, что особенности рельефа в значительной степени влияют на перераспределение снежного покрова. Так, на вогнутых участках толщина снега увеличивается, а на выпуклых-уменьшается, поэтому индекс кривизны поверхности служит эффективным параметром при… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
(25 reference statements)
0
19
1
Order By: Relevance
“…The dominant plants are mosses (Dicranum elongatum, Sphagnum), lichens and vascular plants (such as Carex aquatilis); plant distribution at the site is governed by surface moisture variability (e.g., Hinkel et al, 2003;Zona et al, 2011). There are currently no tall shrubs or woody plants established within the study site, and therefore complex topography is most likely to control the snow depth distribution within the study domain (Sturm et al, 2005;Dvornikov et al, 2015).…”
Section: Study Sitementioning
confidence: 99%
See 4 more Smart Citations
“…The dominant plants are mosses (Dicranum elongatum, Sphagnum), lichens and vascular plants (such as Carex aquatilis); plant distribution at the site is governed by surface moisture variability (e.g., Hinkel et al, 2003;Zona et al, 2011). There are currently no tall shrubs or woody plants established within the study site, and therefore complex topography is most likely to control the snow depth distribution within the study domain (Sturm et al, 2005;Dvornikov et al, 2015).…”
Section: Study Sitementioning
confidence: 99%
“…At each spatial scale, we can compute micro-and macrotopographic metrics such as slope and curvature as well as their correlations with corresponding probe-measured snow depth. The curvature is of particular interest, since Dvornikov et al (2015) reported strong correlations between snow surface curvature and snow depth as well as a dependency of this correlation on the DEM resolution (the lower resolution led to lower correlation coefficients). Note that the DEM resolution (0.5 m) in this study is much higher than the one (25 m) in Dvornikov et al (2015).…”
Section: Spatial Variability Analysis Of Topography and Snow Depthmentioning
confidence: 99%
See 3 more Smart Citations